Left bundle branch area pacing in congenital heart disease. Issue 2 (11th November 2022) - O'Connor, Matthew; Riad, Omar; Shi, Rui; Hunnybun, Dan; Li, Wei; Jarman, Julian W E; Foran, John; Rinaldi, Christopher A; Markides, Vias; Gatzoulis, Michael A; Wong, Tom
Abstract: Aims: Left bundle branch area pacing (LBBAP) has been shown to be effective and safe. Limited data are available on LBBAP in the congenital heart disease (CHD) population. This study aims to describe the feasibility and safety of LBBAP in CHD patients compared with non-CHD patients. Methods and results: This is a single-centre, non-randomized observational study recruiting consecutive patients with bradycardia indication. Demographic data, ECGs, imaging, and procedural data including lead parameters were recorded. A total of 39 patients were included: CHD group ( n = 13) and non-CHD group ( n = 26). Congenital heart disease patients were younger (55 ± 14.5 years vs. 73.2 ± 13.1, P < 0.001). Acute success was achieved in all CHD patients and 96% (25/26) of non-CHD patients. No complications were encountered in either group. The procedural time for CHD patients was comparable (96.4 ± 54 vs. 82.1 ± 37.9 min, P = 0.356). Sheath reshaping was required in 7 of 13 CHD patients but only in 1 of 26 non-CHD patients, reflecting the complex and distorted anatomy of the patients in this group. Lead parameters were similar in both groups; R wave (11 ± 7 mV vs. 11.5 ± 7.5, P = 0.881) and pacing threshold (0.6 ± 0.3 V vs. 0.7 ± 0.3, P = 0.392). Baseline QRS duration was longer in the CHD group (150 ± 28.2 vs. 118.6 ± 26.6 ms, P = 0.002). Despite a numerically greater reduction in QRS and a similar left ventricular activation time (65.9 ± 6.2 vs. 67 ± 16.8 ms, P = 0.840), the QRS remained longer in the CHD group (135.5 ± 22.4 vs. 106.9 ± 24.7 ms, P = 0.005). Conclusion: Left bundle branch area pacing is feasible and safe in CHD patients as compared to that in non-CHD patients. Procedural and fluoroscopy times did not differ between both groups. Lead parameters were satisfactory and stable over a short-term follow-up. Graphical Abstract: Graphical Abstract